2015
DOI: 10.1186/s40555-015-0127-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability of the cranium of Lontra longicaudis (Carnivora: Mustelidae): a morphometric and geographic analysis

Abstract: Background: Studies of morphometric variation make it possible to delimit species and geographic intraspecific variation, mainly in species with wide distribution ranges. In the Neotropical otter, Lontra longicaudis, variation in the shape of the rhinarium of three potential subspecies has been described but it is not known whether there is a pattern to the morphometric variation in the skull throughout the distribution of this species. We analyzed morphological variation in the cranium (ventral view) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
1
16
1
Order By: Relevance
“…Hernández‐Romero et al. () conducted the first study focused on the Neotropical otter's morphological traits. By using a geometric morphometric approach, they evaluated variation in the cranium and mandible of museum specimens representative of a large portion of the species’ range.…”
Section: Genetics and Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hernández‐Romero et al. () conducted the first study focused on the Neotropical otter's morphological traits. By using a geometric morphometric approach, they evaluated variation in the cranium and mandible of museum specimens representative of a large portion of the species’ range.…”
Section: Genetics and Evolutionmentioning
confidence: 99%
“…According to Hernández‐Romero et al. (), the observed morphological variation may be a reflection of different selective pressures acting on both structures in distinct landscapes, influenced by a wide variety of ecological factors. Moreover, their results could be explained by the presence of different evolutionary units delimited by geographic barriers, as is the case with differences in size and shape in Neotropical otter skulls and mandibles from the western Andes and adjacent regions of Orinoco and the Amazon.…”
Section: Genetics and Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The landmark-based geometric morphometrics is acknowledge as the most rigorous and powerful morphometric technique currently available. It has been applied to a variety of structures (e.g., wings, shells, cranial bones, mandibles, premaxilla) and organisms (from insects to mammals) to describe interand intra-specific variation and underlying evolutionary processes [70][71][72][73][74][75][76][77][78]. In A. mellifera, geometric morphometrics of wing vein junctions has been used to discriminate amongst evolutionary lineages and subspecies [2,16,18,19,21], but not to detect genetic structure within subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…Hernadez-Romero et al . [ 8 ] have analyzed geographical variation in Lontra longicaudis (neotropical otter) using geometric morphometrics. The study has included species distributed across South America and found craniodental changes that could be partly due to geographical separation and distance.…”
Section: Discussionmentioning
confidence: 99%